Fintech Adoption and Financial Inclusion Among the Small and Medium Enterprises in Mukono District - Daniella Abang (Uganda Christian University, 2025)
The study examined the effect of Fintech adoption on financial inclusion among the small and medium enterprises in Mukono District. It specifically focused on; identifying the key drivers of fintech adoption and financial inclusion among small and medium enterprises in Mukono, examining the challenges faced during fintech adoption and financial inclusion among small and medium enterprises in Mukono, and examining the opportunities and benefits of fintech adoption among and financial inclusion among small and medium enterprises in Mukono district local government. The study was carried out using a cross sectional survey research design where quantitative research approach was also used. The data was collected using questionnaires and during the data collection, simple random sampling method was used. A sample size of 80 respondents who are owners or managers of the selected SMEs in Kauga, Mukonowas also used in the study. From the findings, it was revealed that even though FinTech uptake and financial inclusion offer Mukono District SMEs enormous benefits such as enhanced credit access, business efficiency, greater market reach, and enhanced management of funds, their full potential is hindered by immense challenges such as poor internet connection, insufficient digital literacy, high-priced services, and poor customer care. The evidence points to the fact that FinTech uptake is extremely reliant on access to technology, the cost of access, regulatory support, and simplicity of platforms. Therefore, in order to unlock the transformative potential of FinTech for SME development, there is a pressing need for interventions that are aimed at improving digital infrastructure, enhancing user education, reducing the cost of services, and enhancing system integration and trust in digital financial systems. Finally, the study recommended the need for expanding internet infrastructure in Mukono District to improve connectivity for SMEs, enhancing digital literacy through targeted training programs, and encouraging FinTech providers to implement affordable pricing models. It also emphasizes the need for robust customer support systems to build user trust and recommends that policymakers promote regulatory frameworks that support interoperability between FinTech and traditional banking systems to foster inclusive and efficient financial access for SMEs.
Undergraduate